1975
DOI: 10.1152/jappl.1975.39.6.900
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary capillary recruitment during airway hypoxia in the dog

Abstract: To study the effect of hypoxia on the pulmonary capillaries, windows were inserted in the chest wall of 9 pentobarbital-anesthetized dogs. A microscope with an image-superimposing device was used to make drawings of the perfused capillaries. Summed lengths of individual perfused capillaries in the drawing were determined with a map-measuring tool. Total capillary length was constant between PaO2 of 160 and 70 Torr. As PaO2 fell below 70 Torr, recruitment of previously unperfused capillaries occurred in every c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…This finding supports the observations of Glazier et al (6) studying rapidly frozen lungs and studies from our own laboratory using in vivo microscopy (3,(24)(25)(26). This pattern of gradual recruitment reflected the average pattern for all of the alveoli (Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This finding supports the observations of Glazier et al (6) studying rapidly frozen lungs and studies from our own laboratory using in vivo microscopy (3,(24)(25)(26). This pattern of gradual recruitment reflected the average pattern for all of the alveoli (Fig.…”
supporting
confidence: 90%
“…In accordance with institutional guidelines, healthy adult male mongrel dogs (20)(21)(22)(23)(24) kg, n ϭ 6) were anesthetized by intravenous injection of pentobarbital sodium dissolved in 0.9% saline (30-40 mg/kg). The animals were intubated and ventilated with room air (Harvard Apparatus 607D).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, ventilated areas with abnormal surfactant may be underperfused with resultant arterial hypoxemia. Severe hypoxia induces pulmonary vasoconstriction mediated by pulmonary arterial vascular small muscle contraction (35)(36)(37). Hypoxia induced vasoconstriction when oxygen saturation is under 50% in all species so far examined (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using other techniques, performed in both experimental animals and humans, have suggested that under conditions of generalised hypoxia there is a redistribution of blood from dependent to nondependent lung regions [32][33][34]. Studies in experimental animals have shown that this redistribution of blood flow is secondary to recruitment of previously unperfused capillaries in these regions, with minimal evidence of capillary dilatation [35]. This recruitment phenomenon has been found to correlate strongly with the increased pulmonary artery pressure [36], secondary to arterial vasoconstriction seen under conditions of generalised hypoxia, with other possible variables (changes in left atrial pressure and cardiac output) having a minimal role.…”
Section: Discussionmentioning
confidence: 99%